Study on the Effectiveness of CCER Mechanism in Serving the Carbon Emissions Trading Market - Sun, Huanhuan; Zhou, Rui; Zhu, Jianfeng (International Journal of Global Economics and Management, 2024)
Based on the relevant data of China’s carbon emissions, this study explores the development status and impact effect of the CCER (China Certified Voluntary Emission Reduction) mechanism in the carbon emissions trading market, reflecting a high degree of professionalism. The study points out that the CCER mechanism, as an important part of the carbon trading market, effectively promotes the activity of the carbon market and the realization of the carbon emission reduction target by incentivizing enterprises to voluntarily reduce emissions and purchase certified emission reductions (CERs) to offset part of the carbon emission quotas. With the gradual promotion of policies and the improvement of market mechanisms, CCER mechanism shows a development path from pilot to full promotion, from voluntary to gradually mandatory. Through data analysis, we find that the price of CCER market is influenced by a variety of factors, including policy orientation, market demand and supply situation. Based on the above research, we put forward corresponding policy recommendations.